Examining of colour Element in Khaghani s âpoetical Works - جهانگیر صفری; فخری زارعی (مطالعات زبانی و بلاغی)
Many years ago, colour as an effective element has been âconsidered in feelings and relations among creatures. At the âlight of psychologists, colours are effective on mental-âpsychological conditions and we can understand the internal âpersonality of people by their tendency of colours.â Poets use colour elements for elaborating their works âand also for exploiting words, poetic pictures and describing âconcepts. Khaghani is one of the poets that used this âphenomenon, frequently. In this article, we try to consider âcolours, quality of its use and also its usages in his poetic art. âIn addition to image-making, Khaghani has used colour in âusage of words, expressions and concepts transferring.â